MODELING THE BRAZILIAN TENSILE STRENGTH TEST OF LIGNITE FROM PESTEANA OPENPIT MINE USING THE COMBINED FINITE-DISCRETE ELEMENT METHOD – FDEM - Ionela Cristina MĂCEŞARU; Alexandru Robert CIOCLU; Florin Dumitru POPESCU (Fiabilitate şi Durabilitate)
Strength is the property of rocks to keep their internal structure unmodified and not deform under the action of a stress. Tensile strength is defined as the maximum tensile stress the rock can endure until its failure and it is usually lower than compressive and shear resistance. The paper presents the simulation of the indirect Brazilian Tensile Strength (BTS) laboratory test for a lignite sample using Geotechnica Irazu software and the Finite-Discrete Element Method – FDEM.